MANAJEMEN FASILITAS PENDIDIKAN DALAM PEMBELAJARAN SEKOLAH MENENGAH KEJURUAN (SMK) - Ahmad Aini; Ahmad Ghaniyyurahman, Ahmad Rijani, Berkatullah Amin, M. Luqman Zulfahnor Said, Syahrani (CV. ADIBA AISHA AMIRA, 2023)
The facilities and infrastructure in schools are the most important part that must be maintained. The quality of a school can also be seen in terms of the completeness of the infrastructure it has, because the existing infrastructure will really support the learning process, academic and non-academic. Therefore, it is necessary to make efforts to provide appropriate advice and infrastructure so that learning activities run well and provide maximum results.